PENGARUH TEORI KONSTRUKTIVISTIK TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA KRISTEN DI SMA - Yosina Aleta Yolanda Mnune; Merlin Filly; Radius W Huseng; Aksa Nesta Naitboho; Hirasius Atama; Indriani Sesfao (JIP: Jurnal Ilmu Pendidikan, 2025)
This study explores how the application of constructivist theory influences student learning outcomes in Christian Religious Education (CRE) at the senior high school level. Constructivist theory emphasizes that students actively build their own knowledge through experiences, discussions, and reflection. In the context of CRE, this approach helps students not only understand theological teachings theoretically but also apply them in real-life situations. This research was conducted through a literature review by analyzing various sources such as journals, books, and previous studies. The findings show that constructivist learning approaches such as case studies, group discussions, and faith-based projects can enhance students’ comprehension, encourage critical thinking, and strengthen their spiritual attitudes and sense of responsibility. Furthermore, students become more engaged, confident in expressing their opinions, and capable of connecting lessons to their personal experiences. These findings highlight the importance of Christian education teachers being creative and reflective in designing learning experiences that are relevant and meaningful for students' faith development during adolescence.